Genetic Characterization of Porcine Circovirus 3 Strains Circulating in Sardinian Pigs and Wild Boars - Silvia Dei Giudici; Giulia Franzoni; Piero Bonelli; Pier Paolo Angioi; Susanna Zinellu; Viviana Deriu; Tania Carta; Anna Maria Sechi; Francesco Salis; Francesca Balzano; Annalisa Oggiano (Pathogens, 2020)
Porcine circovirus 3 (PCV3) is a recently discovered member of the Circoviridae family. So far, its presence has been reported in North America, Asia, South America, and Europe. In this study, blood and tissue samples from 189 Sardinian suids (34 domestic pigs, 115 feral free ranging pigs, and 39 wild boars) were used to genetically characterize the PCV3 strains from Sardinia. PCV3 infection in the animals was confirmed by real time PCR. The detection rate in the three groups analyzed was l7.64% in domestic pigs, 77.39% in free ranging pigs, and 61.54% in wild boars. Moreover, our results showed that co-infection of PCV3 with other viruses is quite a common occurrence. Molecular characterization of Sardinian PCV3 strains was performed by sequencing 6 complete genomes and 12 complete cap genes. Our results revealed that there is a high similarity between our strains and those identified in different countries, confirming the genetic stability of PCV3 regardless of geographical origin. Haplotype network analysis revealed the presence of 6 whole genomes or 12 unique ORF2 haplotypes and a nonsynonymous mutation in ORF2 that leads to an R14K amino acid substitution. Phylogenetic analysis of whole genome and ORF2 was also conducted. The Sardinian strains were allocated in three different clusters of phylogenetic trees of both complete genome and ORF2. With this study, we have provided a snapshot of PCV3 circulation in Sardinia. Our findings might help to achieve a deeper understanding of this emerging porcine virus.